“dosis de ácido húmico granulado de leonardita y ácidos húmicos fulvicos con macro y micro elementos en el cultivo de brocoli (brassica oleracea) sector de quillo allpa-Distrio y provincia de Lamas” - Hidrogo Gonzales, Juan Carlos (2015)
The work of investigation had as aim determine the most efficient dose of acid húmico granulated of Leonardita and acids húmicos and fúlvicos with macro and mike elements, in the production of the culture of hybrid broccoli, Royal Favor F-1 Hyb, in the property in the country ti THE PACIFIC ONE ti of property of the lng. Jorge luís Peláez Rivera, located in the District of Muds, Province of Muds, Department St Martin; latitude South 06 ° 20 ' 15 ", Length West 76 ° 30 ' 45 ", Altitude 835 m.s.n.m.m, zone of lite bs - T; under the design of blocks completely at random with 5 treatments and 3 repetitions; the evaluated variables are % of Emergency, % of capture, height of plant, diameter of the base of the stem, weight of the inflorescence and performance in the production in T.ha-1. The treatment T 4 (50 l.ha-1) obtained the major performance with an average of 15071. 53 kg ha-1, being statistically equal to the treatments T2 (200 kg/ha-1) and T3 (30 l.ha-1) those who reached averages of 14669.17 kg ha-1 and 14466.67 kg ha-1 respectively, All the treatments obtained positiva values for what the benefits (income) were bigger than the investment realized by unit of area and in consequence ali the treatments have generated profit. In general it is possible to increase the profitability with the application of dose of acids húmicos granulated of Leonardita and acids humicos and fulvicos with macro and mike elements.